2011
DOI: 10.1016/j.foodhyd.2010.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Gelatins from three cultured freshwater fish skins obtained by liming process

Abstract: The physico-chemical properties of gelatins from the skins of Red tilapia (Oreochromis nilotica), Walking catfish (Clarias batrachus) and Striped catfish (Pangasius sutchi fowler) obtained through a liming process for 14 days were evaluated. All the gelatins had very mild to undetectable fishy odour and had acceptable colour attributes, which were light yellowish to whitish. The highest gelatin yield (dry basis) was obtained from red tilapia (39.97%) skin and the bloom strength exceeded 300 g. The pH values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
48
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 17 publications
9
48
0
12
Order By: Relevance
“…From Table 1, the gelatin extracted from bighead carp scales showed high gel strength ranged from 490.6 to 656.5 g. This was sharply higher than red tilapia skin gelatin (384.9 g) (Jamilah et al 2011), bovine gelatin(322 g), lizard fish scales gelatin (268 g) (Wangtueai and Noomhorm 2009), porcine skin gelatin (180 g), grass carp fish scales gelatin (276 g) (Zhang et al 2011), siliver carp scales gelatin (152 g) (Wang and Regenstein 2009). These differences between species were possibly due to differences in sample composition, size of the protein chains, as well as complex interactions determined by the amino acids composition (Muyonga et al 2004a).…”
Section: Gel Strengthmentioning
confidence: 95%
“…From Table 1, the gelatin extracted from bighead carp scales showed high gel strength ranged from 490.6 to 656.5 g. This was sharply higher than red tilapia skin gelatin (384.9 g) (Jamilah et al 2011), bovine gelatin(322 g), lizard fish scales gelatin (268 g) (Wangtueai and Noomhorm 2009), porcine skin gelatin (180 g), grass carp fish scales gelatin (276 g) (Zhang et al 2011), siliver carp scales gelatin (152 g) (Wang and Regenstein 2009). These differences between species were possibly due to differences in sample composition, size of the protein chains, as well as complex interactions determined by the amino acids composition (Muyonga et al 2004a).…”
Section: Gel Strengthmentioning
confidence: 95%
“…Ash content on milkfish skin was 2,43%. Jamilah et al (2011) showed that ash content on Red Tilapia (Oreochromis nilotica) skin was 0,51%. The difference of ash content on fish skin is caused by habitat, enviromental, species of fish, sizes, ages etc.…”
Section: Proximate Compositionmentioning
confidence: 99%
“…This result may be associated with the excessive extraction of the yellow bone marrow from the bones in the duck feet due to the high temperature and pressure. Jamilah et al (2011) showed that color values varied with the type of gelatin, and Ahmad (2011) reported that C All values are mean±SD of three replicate. 1) WB: extracted using a water bath; PC: extracted using an electric pressure cooker; MO: extracted using a microwave oven…”
Section: Evaluation Of Colormentioning
confidence: 99%